Fusion to Hydrophobin HFBI Improves the Catalytic Performance of a Cytochrome P450 System - Schulz, Sebastian; Schumacher, Dominik; Raszkowski, Daniel; Girhard, Marco; Urlacher, Vlada B. (Frontiers in Bioengineering and Biotechnology, 2016)
Cytochrome P450 monooxygenases (P450) are heme-containing enzymes that oxidize a broad range of substrates in the presence of molecular oxygen and NAD(P)H. For their activity most P450s rely on one or two redox proteins responsible for the transfer of electrons from the cofactor NAD(P)H to the heme. One of the challenges when using P450s in vitro, especially when non-physiological redox proteins are applied, is the inefficient transfer of electrons between the individual proteins resulting in non-productive consumption of NAD(P)H – referred to as uncoupling. Herein we describe the improvement of the coupling efficiency between a P450 and its redox partner – diflavin reductase – by fusing both enzymes individually to the hydrophobin HFBI – a small self-assembling protein of the fungus Trichoderma reesei. The separated monooxygenase (BMO) and reductase (BMR) domains of P450 BM3 from Bacillus megaterium were chosen as a P450-reductase model system and individually fused to HFBI. The fusion proteins could be expressed in soluble form in E. coli. When HFBI-fused BMO and BMR were mixed in vitro, substantially higher coupling efficiencies were measured as compared to the respective non-fused enzymes. Consequently, myristic acid conversion increased up to 20-fold (after 6 h) and 5-fold (after 24 h). Size exclusion chromatography demonstrated that in vitro the hydrophobin-fused enzymes build multimeric protein assemblies. Thus, the higher activity is hypothesized to be due to HFBI-mediated self-assembly arranging BMO and BMR in close spatial proximity in aqueous solution.